Innovative Didactic Approaches in Teaching Romanian as a Foreign Language (RFL): - Popa, Doinița (Didactica Danubiensis, 2026)
Teaching Romanian as a foreign language (RFL) faces specific challenges generated by the diversity of learners' linguistic and cultural profiles, as well as the need to align with European standards on language competences. The article analyzes the main innovative didactic approaches applicable to teaching RFL, including the communicative-actional paradigm, the integration of digital technologies, the intercultural approach and the use of multimodal resources. The methodological implications and advantages of these directions in the development of communication, autonomy and language transfer skills are highlighted. The study supports the need for an integrative model, focused on competences and the cultural contextualization of the Romanian language.